IMPROVING READING COMPREHENSION SKILLS THROUGH CIRC MODEL ASSISTED BY MIPO POP-UP BOOK MEDIA - Safitri, Tasya Jihan; Kironoratri, Lintang; Fardhani, Much Arsyad (PIONIR: JURNAL PENDIDIKAN, 2024)
This research aims to improve reading comprehension skills through the CIRC model assisted by MIPO pop-up book media in class III students at SD 1 Kaliwungu on the material of determining the main idea of a paragraph. The method used in this research is classroom action research which was carried out over two cycles. Each cycle consists of 2 meetings with 4 stages, namely, planning, implementation, observation and reflection. The subjects of this research were 21 students in class III of SD 1 Kaliwungu. Data collection techniques are observation, interviews, tests, and documentation with quantitative and qualitative data analysis techniques. The findings show that the implementation of the CIRC learning model assisted by MIPO pop-up book media, improves students' reading comprehension skills. Based on the results of pre-cycle research, the average was 69 with a classical completion percentage of 19.04%. Cycle I obtained an average score of 70.71 with a classical completeness percentage of 52.38%. In cycle II there was an increase by obtaining an average value of 79.04 and a classical percentage of 90.47%. Overall the average value of learning outcomes has increased by 8.33. So it can be concluded that by implementing the CIRC learning model assisted by MIPO pop-up book media, it can improve the reading comprehension skills of class III students at SD 1 Kaliwungu.Keywords: Reading comprehension, CIRC, pop-up book